Web services, service-oriented architectures, and cloud computing : the savvy manager's guide - Barry, Douglas K. (Savvy manager's guides., 2013)
Web services are leading to the use of more packaged software either as an internal service or an external service available over the Internet. These services, which will be connected together to create the information technology systems of the future, will require less custom software in our organizations and more creativity in the connections between the services. This book begins with a high-level example of how an average person in an organization might interact with a service-oriented architecture. As the book progresses, more technical detail is added in a "peeling of the onion" approach. The leadership opportunities within these developing service-oriented architectures are also explained. At the end of the book there is a compendium or "pocket library" for software technology related to service-oriented architectures. Only web services book to cover both data management and software engineering perspectives, excellent resource for ALL members of IT teams ; Jargon free, highly illustrated, with introduction that anyone can read that then leads into increasing technical detail ; Provides a set of leadership principles and suggested application for using this technology